Efficiency of Multiple Ovulation and Embryo Transfer (MOET) in a Cattle Farm over a Period of Ten Years in Gujarat - Bhalodia, Sanjay; Patel, Hardik; Patel, Deven; Patil, Shivkumar; C.P., Devanand (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was conducted at Sabarmati Ashram Gaushala, Bidaj, Gujarat. A total of 427 donor animals were investigated over a ten-year period to assess the efficiency of Standard protocol of Multiple Ovulation and Embryo Transfer (MOET). Simultaneously a season wise and breed wise study was also conducted. Breeds studied were Gir, HF, HFCB, Jersey, JYCB, Red Sindhi and Sahiwal. Overall average number of embryos, average number of viable embryos, number of pregnancies and conception rate (%) were found to be 7.8, 4.8, 281 and 39.4, respectively. The year-wise number of pregnancies and conception rates varied from 09 to 42, and 24.6% in 2009-10 to the highest 61.3% in 20014-15, respectively. Further, breed-wise results showed average viable embryo in different breeds as 2.8 in Gir, 4.1 in HF, 5.1 in HFCB, 6.3 in Jersey, 5.8 in JYCB, 3.7 in Red Sindhi and 6.6 in Sahiwal, with corresponding conception rates of 67.7. 34.6, 28.8, 53.1, 39.4, 47.1 and 36.4 %, respectively. A trend was observed that the efficiency of MOET programme was less during monsoon (31.2%) as compared to summer and winter (41.5 and 41.4%).